C70 ordering on nanostructured SrTiO3(001) - Deak, D; Porfyrakis, K; Castell, MR (2007)
The nanostructured (7 x 4) surface of SrTiO3(001) is used as a template to order C70 into single-molecule-wide chains and linear islands. © The Royal Society of Chemistry.